Eptinezumab for the prevention of chronic migraine: efficacy and safety through 24 weeks of treatment in the phase 3 PROMISE-2 (Prevention of migraine via intravenous ALD403 safety and efficacy–2) study - Silberstein, Stephen; Diamond, Merle; Hindiyeh, Nada A.; Biondi, David M.; Cady, Roger; Hirman, Joe; Allan, Brent; Pederson, Susan; Schaeffler, Barbara; Smith, Jeff (Journal of headache and pain, 2020)
Background PROMISE-2 was a phase 3, randomized, double-blind, placebo-controlled study that evaluated the efficacy and safety of repeat intravenous (IV) doses of the calcitonin gene-related peptide–targeted monoclonal antibody eptinezumab (ALD403) for migraine prevention in adults with chronic migraine. This report describes the results of PROMISE-2 through 24 weeks of treatment. Methods Patients received up to two 30-min IV administrations of eptinezumab 100 mg, 300 mg, or placebo separated by 12 weeks. Patients recorded migraine and headache endpoints in a daily eDiary. Additional assessments, including patient-reported outcomes, were performed at regularly scheduled clinic visits throughout the 32-week study period (screening, day 0, and weeks 2, 4, 8, 12, 16, 20, 24, and 32). Results A total of 1072 adults received treatment: eptinezumab 100 mg, n = 356; eptinezumab 300 mg, n = 350; placebo, n = 366. The reduction in mean monthly migraine days observed during the first dosing interval (100 mg, − 7.7 days; 300 mg, − 8.2 days; placebo, − 5.6 days) was further decreased after an additional dose (100 mg, − 8.2 days; 300 mg, − 8.8 days; placebo, − 6.2 days), with both doses of eptinezumab demonstrating consistently greater reductions from baseline compared to placebo. The ≥50% and ≥ 75% migraine responder rates (MRRs) increased after a second dose, with more eptinezumab-treated patients experiencing migraine response than placebo patients (≥50% MRRs weeks 13–24: 100 mg, 61.0%; 300 mg, 64.0%; placebo, 44.0%; and ≥ 75% MRRs weeks 13–24: 100 mg, 39.3%; 300 mg, 43.1%; placebo, 23.8%). The percentages of patients who improved on patient-reported outcomes, including the Headache Impact Test and Patient Global Impression of Change, increased following the second dose administration at week 12, and were greater with eptinezumab than with placebo at all time points. No new safety concerns were identified with the second dose regarding the incidence, nature, and severity of treatment-emergent adverse events. Conclusion Eptinezumab 100 mg or 300 mg administered IV at day 0 and repeated at week 12 provided sustained migraine preventive benefit over a full 24 weeks and demonstrated an acceptable safety profile in patients with chronic migraine. Trial registration ClinicalTrials.gov (Identifier: NCT02974153 ). Registered November 23, 2016.